Evolution Characteristics of Overburden Instability and Failure under Deep Complex Mining Conditions - Xinfeng Wang; Wengang Liu; Xiaojun Jiang; Qiao Zhang; Youyu Wei (Geofluids)
Aiming at the problems of intensified deformation and serious stress damage of stope overburden during mining in deep typical geological environment, taking the deep mining face of a mine in the northwest as the research background, the characteristics and influencing factors of overburden collapse in deep geological environment are analyzed, a comprehensive evaluation system affecting overburden instability and deformation is established, and the temporal and spatial evolution law of deep stope roof failure is obtained by using the “three-zone” distribution theory of overburden, analytic hierarchy process, and numerical simulation method. The results show that high ground stress has the most significant impact on the geological environment of deep stope, followed by the properties of surrounding rock, hydrogeological conditions, and unloading disturbance. The damage degree of the plastic zone at the top of the overburden is greater than that at the bottom. With the increase of mining time, the damage range of the roof and floor gradually increases. In the process of coal seam mining, the increasing range and sinking trend of roof stress are larger near the working face, and the farther away from the working face, the increasing range decreases continuously. The research conclusion provides an important reference for coal seam safety mining and surrounding rock control in complex environments such as deep mining, high stress, and strong disturbance.